Public Olicy Administration and Development - Saxena, Pradeep (Jaipur, India ; Printwell Publishers : Exclusive distributor, Rupa Books, 1988)
With reference to India.
Includes index.
Amirul
Keywords: Policy sciences -- Research -- India; India -- Economic policy -- 1980-1991.; India -- Politics and government -- 1977-